Personality diseases and age: A study with homeless - Salavera, Carlos; Puyuelo, Miguel; Orejudo, Santos (Anales de Psicología / Annals of Psychology, 2009)
In this study, carried out a research on personality disorders in homeless people and their relationship with age. The objective was to analyze whether there is relationship between age and personality disorder suffered by the subject. To do this, a study ex post facto, future-oriented, with a sample of homeless people in a process of integration (N = 77) to which they applied a semi-structured interview and Inventory Millon Clinical Multiaxial (Millon, 1997). The results show how the disorder is the most antisocial present in the overall sample (35.06%), being most preva-lent in children under 30 years (52.63%), decreasing their presence disap-pear with the age of the subject and, there is a high incidence of the disor-der dependent between 30 and 49 years (38.46%) and the narcissistic disorder increases as does the subject's age, reaching 66% in people older than 50 years. Finally, discusses implications of the study in clinical prac-tice and future research.